Q angle values in team and combat athletes - Tural, E.; Imamoglu, O. (International Journal of Applied Exercise Physiology, 2020)
The aim of this study is to compare Q angle values in team and combat athletes. The Quadriceps Q angles of 106 female and 136 male subject were measured in both supine and standing positions by goniometer. It was used t-tests for statistical analyses. Of these, the women were 60 team athletes and 40 combat athletes. In men, there were 72 team athletes and 64 combat athletes. In this study, the average values of Q angle in male athletes are 14.15° in the standing position and 13.10° in the supine position. In female athletes, the average Q angle values were 16.95° in the standing position and 15.31° in the supine position. Q angle values of male athletes and female athletes in supine position showed a statistically significant difference with their foot Q angle values (p <0.001). In this study, the angle Q in women in team athletes is 16.89° in the standing position and 15.12° in the supine position. The Q angle values in women in combat athletes are 17.01° in the standing position and 15.50° in the supine position. In this study, the Q angle in men's athletes is 14.09 degrees in the standing position and 13.06 degrees in the supine position. In combat athletes, the Q angle values in men are 14.21° in the standing position and 13.14° in the supine position. The Q angle values of the team athletes and the combat athletes showed in women and men a statistically significant difference (p <0.05). Again in women and men, the Q angle values of the team athletes and the combat athletes showed in the supine position a statistically significant difference (p <0.05). In this study, in both female athletes and male athletes, the Q angle values of combat athletes are higher than team athletes in both positions. However, it is statistically insignificant for combat athletes to have higher Q angle values than team athletes (p> 0.05). In this study, the Q angle values of both team and combat athletes are higher in males than females. In addition, the Q angle values of team and combat were found to be similar. It can be said that being a team athlete and a combat athlete does not have a significant effect on the height or lowness of the Q angle. However, it is recommended that athletes should be avoided to increase the Q angle in order to have high performance and less injury.